France and the moral panic of "islamo-leftism". (1st September 2022) - Wagener, Albin
Abstract : Since the fall of 2020, the debate on "islamo-leftism" ("islamo-gauchisme" in French) has taken on an important place in both the media and academia. This debate was encouraged by two ministers and has had the effect of highlighting the timid emergence of intersectional work in France, particularly on the topics of race, gender, and class. In this public controversy, a small group of conservative scholars founded the "Observatoire du décolonialisme, " which used the scientific legitimacy of its authors to publicly attack scientific work in a non-scientific manner, as well as grassroots activism movements. If the controversy has since been replaced by ongoing discussions about "wokism, " it has also revealed the construction of a relatively violent discourse on the part of a certain political fringe, on the left as well as on the right, which positions itself in defense of a universalist republican model. This version of the republican model does not support the criticism fed by scientific works using the epistemological framework of intersectionality, which represents a minority in France. The purpose of this article is to study a corpus of press articles, comments from social networks, and texts written by members of the "Observatoire du décolonialisme, " in order to report on the issues and social and political implications of the controversy over "islamo-leftism."